SPEECH DISFLUENCY AND GESTURES PRODUCTION IN UNDERGRADUATE STUDENTS' CONFIDENCE LEVEL OF SPEAKING - Ni Luh Emy Astuti; Ni Nyoman Padmadewi; I Nyoman Adi Jaya Putra (Media Bina Ilmiah, 2024)
Speech disfluency is a type of speech disorder that bothers someone's normal flow of speech. Along with speech disfluency, gestures also accrued during speaking performance. The production of speech disfluency is inseparable from the factors that caused it and the solutions to solve these issues. The study was held at Politeknik Negeri Bali, where the students and lecturer were the participants. Since this study is qualitative research that aims to collect textual data, observation, questionnaires, and interviews were conducted to collect the data. The findings showed that 19 students produced filled pause and 16 students experienced silent pause. There were 9 students who produced repetition and 8 students for repair. Lexical filler was experienced by 7 students and 6 students for prolongation. Meanwhile, there were 19 students produced the beat gesture, 5 students for the iconic gesture, 11 students produced the metaphoric gesture and 5 students for the deictic gesture. Moreover, the cognitive factors were found in 15 students, 17 students were influenced by linguistic factors and 11 students for the affective factors. To create an innovative teaching and learning environment the lecturer combined her method of teaching which used independent study, small-group discussions and brainstorming.